Sexual dysfunction in obese women is more affected by psychological domains than that of non-obese - Paulo José Faria Carrilho; Carla Almeida Vivacqua; Eudes Paiva de Godoy; Selma Sousa Bruno; Alexandra Régia Dantas Brígido; Felipe Chaves Duarte Barros; Maria Bernardete Cordeiro de Sousa (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2015)
Abstract PURPOSE: To compare differences in the occurrence and changed domains of sexual dysfunction in obese and non-obese Brazilian women. METHODS: Female Sexual Function Index, based on six domains, to investigate 31 sexual dysfunction incidence for obese compared to 32 non-obese women, was used. Statistical analysis using ANOVA and MANOVA were performed to compare total scores of Female Sexual Function Index among groups and to identify the differences among domains, Student t -test was used. Statistical significant level was established for all tests for p<0.05. RESULTS: No difference in female sexual dysfunction frequency between obese (25.8%) and non-obese women (22.5%) was found. However, an important distinction in which aspects of sexual life were affected was found. While the obese group was impaired in three domains of sexual life (desire, orgasm, and arousal), in the control group five aspects were dysfunctional (desire, orgasm, arousal, pain and lubrication). Future research exploring psychological outcomes in obese females, such as body image and measures of positive and negative effect, might better characterize the female sexual dysfunction in this group. CONCLUSIONS: Obesity does not appear to be an independent factor for allow quality of female sexual life. However, disturbance associated to obesity indicates a low frequency of disorder in physical domains, suggesting that psychological factors seem to be mainly involved in the sexual dysfunction in obese women.